2012
DOI: 10.1007/s12011-012-9329-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper in Organic Proteinate or Inorganic Sulfate Form is Equally Bioavailable for Broiler Chicks Fed a Conventional Corn–Soybean Meal Diet

Abstract: An experiment was conducted to investigate the bioavailability of organic copper (Cu) proteinate relative to inorganic Cu sulfate for broiler chicks fed a conventional corn-soybean meal basal diet. A total of 320 day-old Arbor Acres commercial male chicks were assigned to one of five treatments in a completely randomized design involving a 2 × 2 factorial arrangement with two levels of added Cu (125 or 250 mg Cu/kg) and two Cu sources (Cu proteinate and Cu sulfate) plus a control with no added Cu for an experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…There were no differences in the weight gain, feed intake, and FCR, and it may show that the levels of dietary Cu were much higher than the requirement. In agreement, Liu et al [17] reported no improvement in growth performance and feed intake in broiler chickens by supplementating 125 or 250 mg/kg copper sulfate, whereas the concentration of Cu in the plasma and liver were linealy increased.…”
Section: Discussionsupporting
confidence: 61%
“…There were no differences in the weight gain, feed intake, and FCR, and it may show that the levels of dietary Cu were much higher than the requirement. In agreement, Liu et al [17] reported no improvement in growth performance and feed intake in broiler chickens by supplementating 125 or 250 mg/kg copper sulfate, whereas the concentration of Cu in the plasma and liver were linealy increased.…”
Section: Discussionsupporting
confidence: 61%
“…Chemical characteristics are considered important in predicting the bioavailabilities of chelated and complexed metals. A series of studies from our laboratory (Li et al, 2004(Li et al, , 2005Huang et al, 2009Huang et al, , 2013Wang et al, 2012;Liu et al, 2012a; has shown that the bioavailabilities of organic Mn, Zn, Cu, and Fe were closely related to their Q f values. Holwerda et al (1995) classified the organic trace mineral supplements with their Q f into 4 classes, in which the supplements with Q f values less than 10 have a weak chelation strength, those with Q f values between 10 and 100 have a moderate chelation strength, those with Q f values between 100 and 1,000 have a strong chelation strength, and those with Q f values greater than 1,000 have an extremely strong chelation strength.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical characteristics of organic Fe sources may partially explain the discrepancies in their relative bioavailabilities. A series of studies from our laboratory (Li et al, 2004(Li et al, , 2005Huang et al, 2009Huang et al, , 2013Liu et al, 2012aLiu et al, , 2013Wang et al, 2012) have shown that the relative bioavailabilities of organic Mn, Zn, and Cu for broilers fed a conventional corn-soybean meal diet were closely related to their chelation strengths (quotient of formation [Q f ] values). The latest study from our laboratory demonstrated that iron proteinate with moderate chelation strength had a higher bioavailability than iron sulfate in enhancing hemoglobin (Hb) and total body Hb Fe of broilers fed a caseindextrose diet.…”
mentioning
confidence: 99%
“…To test the effect of supplemental Se, data were analysed using single degree of freedom contrast to compare all supplemental Se treatments with the control (Liu et al., ). Data excluding the control were further analysed as a 2 × 3 (source × level) factorial arrangement of treatments by two‐way analysis of variance with a model including the main effects of Se source, Se level and their interaction using the general linear model (GLM) procedure of the SPSS 17.0 (Statistical Product and Service Solutions Corp., Chicago, IL, USA) for Windows.…”
Section: Methodsmentioning
confidence: 99%